Genetic variants of adiponectin and risk of colorectal cancer. Issue 1 (8th December 2014) - Song, Mingyang; Gong, Jian; Giovannucci, Edward L.; Berndt, Sonja I.; Brenner, Hermann; Chang‐Claude, Jenny; Curtis, Keith R.; Harrison, Tabitha A.; Hoffmeister, Michael; Hsu, Li; Jiao, Shuo; Le Marchand, Loic; et al.
Abstract : Circulating adiponectin has been associated with lower risk of colorectal cancer (CRC). Genome‐wide association studies have identified several single‐nucleotide polymorphisms (SNPs) associated with adiponectin levels. However, it is unclear whether these SNPs are associated with CRC risk. In addition, previous data on SNPs in the adiponectin pathway and their associations with CRC are inconsistent. Therefore, we examined 19 SNPs in genes related to adiponectin or its receptors and their associations with CRC using logistic regression among 7, 020 cases and 7, 631 controls drawn from ten studies included in the Genetics and Epidemiology of Colorectal Cancer Consortium. Using data from a subset of two large cohort studies, we also assessed the contribution of individual SNPs and an adiponectin genetic score to plasma adiponectin after accounting for lifestyle factors among 2, 217 women and 619 men. We did not find any statistically significant association between the 19 adiponectin‐associated SNPs and CRC risk (multivariable‐adjusted odds ratios ranged from 0.89 to 1.05, all p  > 0.05). Each SNP explained less than 2.50% of the variance of plasma adiponectin, and the genetic score collectively accounted for 2.95 and 1.42% of the variability of adiponectin in women and men, respectively, after adjustment for age, body mass index, physical activity, smoking, alcohol consumption, regular use of aspirin or nonsteroidal anti‐inflammatory drug and postmenopausal hormone use. In conclusion, our findings do not support an association between known adiponectin‐related common SNPs and CRC incidence. However, known common SNPs account for only a limited proportion of the interindividual variance in circulating adiponectin. Further work is warranted to investigate the relationship between adiponectin and CRC while accounting for other components in the pathway. Abstract : What's new? Obesity is a well‐established risk factor for colorectal cancer, and mounting evidence suggests that the adipocyte‐derived hormone adiponectin is behind that link. In the present investigation, common genetic variants in the adiponectin ( ADIPOQ ) gene were analyzed for potential relationships with colorectal cancer risk. However, no statistically significant associations were identified. Because common genetic determinants account for only a limited proportion of the variance in circulating adiponectin concentrations, factors that influence adiponectin receptors and other components of the adiponectin pathway should be investigated.